1998
DOI: 10.4269/ajtmh.1998.58.330
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatitis E virus in sporadic cases of acute and fulminant hepatitis in an endemic area (Chad).

Abstract: Abstract. Forty-one patients with acute or fulminant hepatitis and 86 control patients were entered into a study of sporadic, acute, and fulminant hepatitis in the N'Djamena area of Chad in 1993. Acute hepatitis B was diagnosed in nine (22%) patients and acute hepatitis E in 27 (66%) patients. No acute hepatitis A was observed and 10% of the patients had serologic markers of hepatitis C virus (HCV) infection. Dual acute hepatitis B and E were observed in four patients (10%) and acute HEV infection was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 27 publications
3
36
1
Order By: Relevance
“…16 HEV is predominantly transmitted through contaminated water and food. [1][2][3][4][5][6][7]14,15,[17][18][19][20][21] The disproportionate pregnancy rate among the women and girls with ALF in the current study may raise the suspicion of sexual transmission of HEV. However, sexual transmission of HEV has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…16 HEV is predominantly transmitted through contaminated water and food. [1][2][3][4][5][6][7]14,15,[17][18][19][20][21] The disproportionate pregnancy rate among the women and girls with ALF in the current study may raise the suspicion of sexual transmission of HEV. However, sexual transmission of HEV has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…29 Possibly analogous increased severity of hepatitis A and B has been ascribed to pregnancy-related depression of cell-mediated immunity. 31 Coursaget and others 11 speculate that the superimposition of acute HEV on chronic liver disease caused by HBV may lead to acute or fulminant hepatitis in some patients, including pregnant women. In Chad, these authors found that of 35 patients with sporadic acute or fulminant hepatitis E, 21 (60%) and 5 (14%) had sero-logical evidence of, respectively, chronic and acute hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis B virus surface antigen was present in 30% of controls. 11 Hepatitis B virus infection is hyperendemic in Kavango; a 1983 study demonstrated that 98% of the population showed some serological evidence of exposure, with a 13.6% carriage rate of HBV surface antigen. 28 Our small sample (Table 2) showed no significant difference (P ϭ 0.81, Fisher's exact test) between patients with overt hepatitis and normal controls with regard to HBV surface antigen carriage, but a much larger study would be required to investigate any association.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations